A Study on Buying Behaviour of Rural Families with the Purchase of Durable goods in Tamil Nadu - Arul Rajan, Dr. K. (Journal of Contemporary Research in Management (JCRM), 2015)
A Study on Buying Behaviour of Rural Families with the Purchase of Durable goods in Tamil Nadu